Lectura heterodoxa de la transformación digit al europea del turismo: Paradojas y fallos por el cambio de modelo - Antonio Sánchez-Bayón (Atlantic Review of Economics (ARoEc), 2022)
– This is a critical - hermeneutic and historical - comparative study of Political Economy on the evolution of the tourism sector in Europe, with special attention to the Spanish case. Despite t he economic importance of tourism and the deep changes stimulated by globalization and digitization, this sector is still not recognized as a sufficient entity; in addition it is losing the opportunity for its transformation and adaptation to talent capita lism. The theoretical and methodological frameworks of the heterodox synthesis are used, combined the Austrian School with the New - Institutional Approach. Finally, there is a reflection on the Next Gen EU funds management and its impact on tourism.
Keywords: B5; D73; E24; I31; L83; M48; O3; Z1; 330